Immunoregulatory Aspects of Immunotherapy - Shamsadin Athari, Seyyed (IntechOpen, 2018)
Immunotherapy is an innovative, leading and valuable approach to the treatment and control of many diseases. It can solve many problems of public health worldwide. Many people in numerous countries are suffering from a wide range of diseases (communicable and non-communicable) that can be cured or controlled by the immune system and immunotherapy. Some immunological diseases (i.e. allergic reactions and asthma, autoimmune disease, immunodeficiency disease, hypersensitivity reactions, etc.) have immune response pathophysiology and by controlling immune system mechanisms, these diseases can be controlled and cured. Immunoregulatory Aspects of Immunotherapy focuses on immune system mechanism, diagnosis, treatment and other related problems. The chapters have applicable and scientific data in immunotherapeutic approaches based on medical sciences, and would be of benefit to all researchers in immunology, allergy and asthma fields. The book discusses the prevention, diagnosis, treatment and follow-up of patients who have dangerous diseases. We hope this book will be a new approach to the immunotherapy of diseases and will improve public health and wellbeing.